Analysis of the Impact of Academic Supervision and Prasarana Tools on Teacher Performance: The Mediation Role of Teacher Competence - Susilaningsih; Djoko Soelistya; Suyoto (South Sulawesi Education Development (SSED), 2024)
This study is carried out to determine the factors that influence employees' intentions to leave their jobs in firms. The objective is to examine the impact of organizational culture and working environment on turnover intentions, with job satisfaction serving as a mediator. The research methodology employed in this study is quantitative, with a focus on a specific demographic. The sample for this study consisted of 271 employees from a corporation. The research findings indicated that both Organizational Culture and Working Environment have a positive and significant impact on Turnover intention. Organizational Culture also has a positive and significant effect on Job Satisfaction, while the Labor Environment does not significantly affect job satisfaction. Working Satisfying has a significant and positive influence on turnover intentions. Organizational culture has a meaningful impact on Turnover intentions through partial employment satisfaction as a mediator, and the working environment has a significant influence on turnover intensities through partial employee satisfaction. This implies that both the work culture and the work environment need to be consistent and comfortable within the organization's setting in order to reduce turnover intention. To achieve this, the company should maintain a consistent organizational culture and commitment, while ensuring that the work facilities are in harmony at the workplace.